Clinical heterogeneity in patients with idiopathic blepharospasm: A cluster analysis. (July 2017) - Defazio, G.; Conte, A.; Gigante, A.F.; Ferrazzano, G.; Pellicciari, R.; Dagostino, S.; Fabbrini, G.; Berardelli, A.
Abstract: Background: Idiopathic blepharospasm is a clinically heterogeneous condition. It is not known whether the various manifestations become manifest sequentially during the course of the disease or aggregate in separate clusters identifying subpopulations of patients. Methods: Eighty-nine patients with idiopathic blepharospasm were assessed using k-means cluster analysis to identify relatively homogeneous groups on the basis of low-intragroup/high-intergroup differences across a set of selected variables. Results: The results suggest that there may be three groups of patients. Group 1 included patients who had prolonged muscle spasms leading to complete rim closure associated with brief and/or prolonged spasms with incomplete rim closure, the most severe blepharospasm, and a greater tendency to spread to adjacent segments. Group 2 included patients characterized by prolonged spasms with partial rim closure, either alone or associated with brief spasms whereas Group 3 included patients with brief spasms with complete rim closure, the least severe blepharospasm, and the lowest tendency to spread. The severity of Group 2 blepharospasm was between that observed in Group 1 and Group 3, while the tendency to spread was similar to Group 3. The three groups did not differ for disease duration, age of onset, sex and other clinical features. The observation that inhibition of the R2 component of the blink reflex recovery cycle was more abnormal in Groups 1/2 2 than in Group 3 at least in part validates our classification. Conclusions: The present study suggests that blepharospasm patients may be classified in different subtypes according to the type of spasms, severity of the condition and tendency to spread. Highlights: Idiopathic blepharospasm is a clinically heterogeneous condition. We used cluster analysis to check for separate clusters of patients. We identified 3 types of patients according to spasm type and tendency to spread.